A Complex shaped crucible frame structure modelling and finite element analysis for stress and deformation - V. Dhandapani, N; Manimaran, R; C. Uvaraja, V; Sridhararan, R (International Journal of Engineering and Technology, 2018)
Crucible frame structures are otherwise called as complex frame structures and its study is needed for further improvement in the emerging technology. The frame structure are frequently used an operational system support ofÂ  other mechanisms of a physical construction and/or steel frame that limits the assembly's extent in this study crucible frame structures are analysed using Finite element analysis and the results are expected in terms of safety for actual use. Based on ANSYS Software, the crucible structure can be meshed (discretized into several parts are called elements). At last, we can apply the boundary conditions and calculate its maximum deformation by applying various loads.